Real-time PCR-based Detection of Foodborne Pathogen Cronobacter sakazakii DNA in Infant Formula Milk with Specific Targeting on the hfq Gene - Nurjayadi, Muktiningsih; Juliansyah, Dandy Akbar; Declan, Jefferson Lynford; Putri, Gladys Indira; Krisdawati, Ismaya; Rahmawati, Atikah Nur; Azzahra, Maharanianska; Maulana, Irvan; Putri, Gusti Angieta; Kurniadewi, Fera; Kartika, Irma Ratna; Saamia, Vira; Wiranatha, I Made; Abomoelak, Bassam; El-Enshasy, Hesham Ali (HAYATI Journal of Biosciences, 2025)
Cronobacter sakazakii has been linked to cause meningitis, necrotizing enterocolitis, and sepsis in infants and newborns, with case fatality rates ranging from 40 to 80%. The most common source of infection has been identified as Cronobacter sakazakii-contaminated infant formula. With a relatively specific target hfq gene, this study aims to develop a real-time PCR method to identify Cronobacter sakazakii in infant formula milk. Real-time PCR is used as a detection method because rt- PCR has higher specificity and sensitivity compared to conventional PCR methods. The real-time PCR method also has a higher level of effectiveness and time efficiency compared to conventional PCR. Cronobacter sakazakii ATCC 29544 genomic DNA was isolated and used in a real-time PCR assay. Cronobacter sakazakii DNA was amplified using a primer targeting the hfq gene, yielding a 145 bp amplicon. The results of the real-time PCR test showed that Cronobacter sakazakii DNA with a concentration of 53 ng/µL could be amplified by the primer pairs of hfq gene with Ct values of 11 respectively then had Tm values of 81.7°C±0.5. The specificity test showed that the hfq primer pairs could differentiate between the target and some non-target bacteria. The sensitivity test showed the ability of the primer to detect the smallest concentration of 3.392 pg/µL with a Ct of 26.16. Based on the results obtained, it can be concluded that the hfq primer has the potential to be used as a fast detection method for Cronobacter sakazakii bacteria in infant formula using real-time PCR.